Male sexual dysfunction in Asia - Ho, Christopher CK (Nature Publishing Group, 2011)
Sex has always been a taboo subject in Asian society. However, over the past few years, awareness in the field of men's sexual health has improved, and interest in sexual health research has recently increased. The epidemiology and prevalence of erectile dysfunction, hypogonadism and premature ejaculation in Asia are similar in the West. However, several issues are specific to Asian males, including culture and beliefs, awareness, compliance and the availability of traditional/complementary medicine. In Asia, sexual medicine is still in its infancy, and a concerted effort from the government, relevant societies, physicians and the media is required to propel sexual medicine to the forefront of health care.